Attenuated Modified Vaccinia Virus Ankara Can Be Used as an Immunizing Agent under Conditions of Preexisting Immunity to the Vector - Ramírez, Juan C. (American Society for Microbiology, 2000)
A problem associated with the use of vaccinia virus recombinants as vaccines is the existence of a large human population with preexisting immunity to the vector. Here we showed that after a booster with attenuated recombinant modified vaccinia virus Ankara (rMVA), higher humoral and cellular immune responses to foreign antigens (human immunodeficiency virus type 1 Env and β-galactosidase) were found in mice preimmunized with rMVA than in mice primed with the virulent Western Reserve strain and boosted with rMVA. This enhancement correlated with higher levels of expression of foreign antigens after the booster.